2020
DOI: 10.1016/j.marpolbul.2020.111722
|View full text |Cite
|
Sign up to set email alerts
|

Using Copernicus Sentinel-2 and Sentinel-3 data to monitor harmful algal blooms in Southern Chile during the COVID-19 lockdown

Abstract: During the southern summer of 2020, large phytoplankton blooms were detected using satellite technology in Chile (western Patagonia), where intensive salmonid aquaculture is carried out. Some harvesting sites recorded massive fish mortalities, which were associated with the presence of the dinoflagellate species Cochlodinium sp. The bloom included other phytoplankton species, as Lepidodinium chlorophorum, which persistently changed the colour of the ocean to green. These blooms coincided with the government-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 56 publications
(79 reference statements)
0
24
0
Order By: Relevance
“…The lack of surveillance could result in the proliferation of toxic dinoflagellate blooms that can cause mass mortalities in cage aquaculture located in rivers, estuaries, or coastal waters [90]. Rodríguez-Benito et al [91] reported mass fish mortalities in intensive salmonid aquaculture due to harmful algal blooms consisting of toxic dinoflagellates, Cochlodinium sp. and Lepidodinium chlorophorum, that occurred during the COVID-19 lockdown period resulting in a loss of USD 800 million.…”
Section: Covid-19 and Aquaculture Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of surveillance could result in the proliferation of toxic dinoflagellate blooms that can cause mass mortalities in cage aquaculture located in rivers, estuaries, or coastal waters [90]. Rodríguez-Benito et al [91] reported mass fish mortalities in intensive salmonid aquaculture due to harmful algal blooms consisting of toxic dinoflagellates, Cochlodinium sp. and Lepidodinium chlorophorum, that occurred during the COVID-19 lockdown period resulting in a loss of USD 800 million.…”
Section: Covid-19 and Aquaculture Industrymentioning
confidence: 99%
“…For the monitoring of ecosystem events, Rodríguez-Benito et al [91] demonstrated the use of satellite technology for the monitoring of harmful algal bloom in aquaculture areas during the lockdown period as an early warning system to prevent mass fish mortality. Remote sensing-based observation also shows promise, as it measures TSS (total suspended solids) concentrations in natural waters with high spatial and temporal resolutions that can cover all the scales of variability and identify the spatiotemporal extent of TSS [132,133].…”
Section: Monitoringmentioning
confidence: 99%
“…In another hemisphere, Sentinel‐2 and Sentinel‐3 imagery was applied to detect a harmful algal bloom in salmonid aquaculture in Chile. The analysis technique, combined with rapid delivery of the high‐resolution satellite imagery, allowed for near real‐time monitoring and decision‐making when in‐situ sampling was restricted by a mandated lockdown (Rodríguez‐Benito, Navarro, & Caballero, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of satellite imagery provides a complementary monitoring tool, supplies high spatial and temporal resolution water quality data, and greatly improves our understanding of variations in water quality in the reservoir, which generates highly relevant information for managers. In addition, this need for monitoring is increased by events such as pandemics or disasters [28]. On the one hand, ordinary but frequent sensors like Terra/Aqua MODIS provide daily observations but with coarse spatial resolutions (e.g., 250 ma 1000 m) that cannot reveal spatial details of CyanoHABs in small reservoirs.…”
Section: Introductionmentioning
confidence: 99%